French artisan food co-operatives at the intersection between the artisan dimension and industrial logic – A two case study analysis - Simon Adderley; Lee Gray (Research Synergy Foundation, 2020)
This article provides two case studies of food manufacturing co-operatives in France. Both co-operatives were formed after large multi-national firms ceased manufacturing in a specific factory and the workers, rather than accepting redundancies, established an artisan production company based on “traditional” techniques and co-operative values. In order to do this it utilises the often overlooked literature of the artisan craft movement. While this literature has been primarily developed around the emergence of artisanship in the third world it will be argued that such conceptualisations are also useful when exploring the development of artisanship amongst co-operative companies who are re-establishing their traditional ways of working, even in the “developed world”. In doing so it builds on the work of Dickie and Frank (1996) who stated that “through crafts, tradition is maintained and/or invented, and marketed to consumers who find other meanings in the objects.” The theoretical construct posited by this article maintains that businesses with non-traditional economic models actually faced a complex and multi-faceted series of pulls in a number of different directions. Furthermore that businesses re-establishing themselves as artisan manufacturers using locally sourced materials with democratic models of governance can be directly compared to artisan craft producers from the developing world. The article draws attention to the parallels between two important research areas which have not been linked before. By doing so it has important implications for the mechanisms by which support is given to emerging co-operatives in the developed world and the a priori assumptions which underpin current policy.